THE CREATION OF A GAS SENSITIVE SEMOCONDUCTOR SENSOR ON THE BASE OF A MATERIAL, FORMED BY ZOL-GEL METHOD USING ETHANDIOL-1,2: UDC 543.272.2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
A Sol-Gel technology approach was used for creation of a sensitive layer of a semiconductor gas sensor on the base of SnO2 doped with Sb2O5 additives (0,15 mol %). Ethanediole-1,2 was utilized in the capacity of a solvent and substituting reagent. On the base of the obtained material a sensor was fabricated and dependence of its signal on the H2 concentration in air was studied. Higher sensitivity of the sensor towards 40 ppm of H2 in air was observed comparing to a sensor made on the base of material obtained via traditional co-sedimentation-from-water method.
Keywords: -